Head Impacts during the Direct Frontal (Forehead) and Side (Temple) Collision - Human vs. Hybrid III Dummy - Tomsovsky, Lubos; Literova, Lucie; Kubovy, Petr; Lopot, Frantisek; Havlicek, Martin; Stocek, Ondrej; Fara, Lukas; Jezdik, Roman; Purs, Hynek; Tikkanen, Tommi; Novak, Martin; Jelen, Karel (Manufacturing Technology Journal, 2023)
The paper is focused on the dynamic response of a Hybrid III crash-test dummy during low-severity frontal (forehead) and side (temple) head impacts. The measurements used a pedestrian dummy (Hybrid III 50th percentile male dummy, Jasti Co., ltd., Tokyo, Japan) and a unique pendulum impact testing machine (impactor) of own design and construction. The tests were conducted at two various impact intensities (velocities) that did not exceed the speed of 1.6 m.s-1. The primary outcome variable was a resultant magnitude of acceleration measured on the vertex of the dummy's head and the results were compared to 11 human volunteers. The goal of the study was to analyze the biofidelity of the Hybrid III Dummy in a pedestrian setting during low-severity frontal and side head impacts by comparing the dynamics and kinematics of the dummy's head to human volunteers.
Keywords: Dummy; Pedestrian; Crash Tests; Biofidelity; Tram; Head impact